Discovery and lead optimisation of a potent, selective and orally bioavailable RARβ agonist for the potential treatment of nerve injury. Issue 8 (15th April 2019) - Goncalves, Maria B.; Clarke, Earl; Jarvis, Christopher I.; Barret Kalindjian, S.; Pitcher, Thomas; Grist, John; Hobbs, Carl; Carlstedt, Thomas; Jack, Julian; Brown, Jane T.; Mills, Mark; Mumford, Peter; et al.
Graphical abstract: Abstract: Oxadiazole replacement of an amide linkage in an RARα agonist template 1, followed by lead optimisation, has produced a highly potent and selective RARβ agonist 4-(5-(4, 7-dimethylbenzofuran-2-yl)-1, 2, 4-oxadiazol-3-yl)benzoic acid (10 ) with good oral bioavailability in the rat and dog. This molecule increases neurite outgrowth in vitro and induces sensory axon regrowth in vivo in a rodent model of avulsion and crush injury, and thus has the potential for the treatment of nerve injury.